Biorefinery Concept Employing Bacillus coagulans: LX-Lignin and L-(+)-Lactic Acid from Lignocellulose - Linda Schroedter; Friedrich Streffer; Katrin Streffer; Peter Unger; Joachim Venus (Microorganisms, 2021)
A new biorefinery concept is proposed that integrates the novel LX-Pretreatment with the fermentative production of L-(+)-lactic acid. Lignocellulose was chosen as a substrate that does not compete with the provision of food or feed. Furthermore, it contains lignin, a promising new chemical building material which is the largest renewable source for aromatic compounds. Two substrates were investigated: rye straw (RS) as a residue from agriculture, as well as the fibrous digestate of an anaerobic biogas plant operated with energy corn (DCS). Besides the prior production of biogas from energy corn, chemically exploitable LX-Lignin was produced from both sources, creating a product with a low carbohydrate and ash content (90.3% and 88.2% of acid insoluble lignin). Regarding the cellulose fraction of the biomass, enzymatic hydrolysis and fermentation experiments were conducted, comparing a separate (SHF), simultaneous (SSF) and prehydrolyzed simultaneous saccharification and fermentation (PSSF) approach. For this purpose, thermophilic B. coagulans 14-300 was utilized, reaching 38.0 g L−1 LA in 32 h SSF from pretreated RS and 18.3 g L−1 LA in 30 h PSSF from pretreated DCS with optical purities of 99%.